TOPICAL ISSUES OF THE DEVELOPMENT OF SCIENTIFIC AND EDUCATIONAL ACTIVITIES IN THE HIGHER EDUCATION SYSTEM OF THE NORTH CAUCASUS FEDERAL DISTRICT (part 2) - A. Borisenko (Вестник Северо-Кавказского федерального университета, 2022)
Based on the analysis of the main directions of development of scientific and educational activities in the higher education system of the NCFD, taking into account the goals and objectives of digital transformation, the most important measures and mechanisms of its educational, methodological and scientific components are highlighted in the article. It is shown that the basis for qualitative transformations of the scientific and educational process can be based on a system ofpersonalization oftraining, a project-oriented approach using modern information technologies, the development of digital competencies, non-core skills and sustainable motivation of teachers and students to participate in research work, a system of digital support for branch scientific directions. Special attention is paid to the interdisciplinary nature ofthe development of scientific and educational activities in the conditions of full-scale development of digital technologies.